NHECD - Nano Health and Environmental Commented Database - Maimon, Oded; Browarnik, Abel (Data Mining and Knowledge Discovery Handbook, 2010)
The impact of nanoparticles on health and the environment is a significant research subject, driving increasing interest from the scientific community, regulatory bodies and the general public.We present a smart repository system with text and data mining for this domain. The growing body of knowledge in this area, consisting of scientific papers and other types of publications (such as surveys and whitepapers) emphasize the need for a methodology to alleviate the complexity of reviewing all the available information and discovering all the underlying facts, using data mining algorithms and methods. The European Commission-funded project NHECD (whose full name is “Creation of a critical and commented database on the health, safety and environmental impact of nanoparticles”) converts the unstructured body of knowledge produced by the different groups of users (such as researchers and regulators) into a repository of scientific papers and reviews augmentedby layers of information extracted from the papers. Towards this end we use taxonomies built by domain experts and metadata, using advanced methodologies.We implement algorithms for textual information extraction, graph mining and table information extraction. Rating and relevance assessment of the papers are also part of the system. The project is composed of two major layers, a backend consisting of all the above taxonomies, algorithms and methods, and a frontend consisting of a query and navigation system. The frontend has web interface which address the needs (and knowledge) of the different user groups. Documentum, a content management system (CMS), is the backbone of the backend process component. The frontend is a customized application built using an open source CMS. It is designed to take advantage of the taxonomies and metadata for search and navigation, while allowing the user to query the system, taking advantage of the extracted information.